2006
DOI: 10.1017/s0012162206002118
|View full text |Cite
|
Sign up to set email alerts
|

Differences in finger length ratio between males with autism, pervasive developmental disorder–not otherwise specified, ADHD, and anxiety disorders

Abstract: Children with autism have a relatively shorter index finger (2D) compared with their ring finger (4D). It is often presumed that the 2D:4D ratio is associated with fetal testosterone levels and that high fetal testosterone levels could play a role in the aetiology of autism. It is unknown whether this effect is specific to autism. In this study, 2D:4D ratios of 144 males aged 6 to 14 years (mean age 9y 1 mo [SD 1y 11 mo]) with psychiatric disorders were compared with those of 96 males aged 6 to 13 years from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
108
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 20 publications
15
108
3
3
Order By: Relevance
“…Fourth, masculinized finger-length patterns appeared to be more specific to the domain of inattention than hyperactivity-impulsivity in boys and girls when the shared variance between the two symptom domains was eliminated. Controlling for, or covarying, ethnicity did not alter the results.These findings are consistent with recent studies in humans indicating that ADHD symptoms may be related to more masculinized finger-length ratios (de Bruin et al, 2006;Fink et al, 2007;McFadden et al, 2005;Stevenson et al, 2007;Williams et al, 2003). However, the present findings contradict several studies that found these relations in girls but not boys (Fink et al, 2007;Stevenson et al, 2007;Williams et al, 2003).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Fourth, masculinized finger-length patterns appeared to be more specific to the domain of inattention than hyperactivity-impulsivity in boys and girls when the shared variance between the two symptom domains was eliminated. Controlling for, or covarying, ethnicity did not alter the results.These findings are consistent with recent studies in humans indicating that ADHD symptoms may be related to more masculinized finger-length ratios (de Bruin et al, 2006;Fink et al, 2007;McFadden et al, 2005;Stevenson et al, 2007;Williams et al, 2003). However, the present findings contradict several studies that found these relations in girls but not boys (Fink et al, 2007;Stevenson et al, 2007;Williams et al, 2003).…”
supporting
confidence: 90%
“…Boys with ADHD had more masculine digit ratios than control boys, F(3, 144) = 2.78, p < .05, η 2 = 0.06), whereas the effect in girls was trivial in size (η 2 = 0.02) and nonsignificant. This last finding was consistent with studies that examined these associations in clinically diagnosed samples (de Bruin et al, 2006;McFadden et al, 2005), but it contradicts other work utilizing rating scale data in nondiagnosed samples (Fink et al, 2007;Stevenson et al, 2007;Williams et al, 2003). We conducted bivariate correlations, shown in Table 3, to examine whether more masculine (i.e., lower) finger-length ratios were related to more inattentive or hyperactive-impulsive ADHD symptoms in the total group of children (i.e., boys and girls examined together).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…147 However, no significant correlation was found with neonatal testosterone levels in a cohort study.…”
Section: Prenatal Testosteronementioning
confidence: 89%
“…Other investigators have used image analysis to determine 2D:4D from images obtained from flatbed scanners (Bailey and Hurd, 2005;de Bruin et al, 2006;McFadden and Shubel, 2002), radiographs (McIntyre et al, 2005, and digital photographs (Honekopp et al, 2006a;Pokrywka et al, 2005). Bailey and Hurd (2005) showed good intraobserver reliability when a single observer measured finger lengths in 10 subjects using computer-assisted image analysis on hand scans while McFadden and Shubel (2002) showed good interobserver reliability when three observers measured finger lengths using similar computer-based calipers on scanned images of the hand.…”
Section: Discussionmentioning
confidence: 99%